Patients With Drug-Naive Bipolar Disorder in Remission After 8 Weeks of Treatment Had Decreased Serum Uric Acid Concentrations - Chen, Jingxu; Chen, Hongmei; Zhang, Ligang; Tan, Yunlong; Wang, Shaoli; Jones, Alison; Yang, Fude; Huang, Xu-Feng (Frontiers in Psychiatry, 2019)
Background Evidence indicates that the serum concentration of uric acid (UA) in patients may relate both to the pathophysiology and therapeutics of bipolar disorder (BPD). The purpose of this study was to examine the changes and clinical significance of serum UA concentrations in first-episode manic patients suffering from BPD. Methods Seventy-six drug-naive patients with first-episode bipolar mania and seventy-six age- and gender- matched healthy subjects were recruited. Young Mania Rating Scale (YMRS) and Hamilton Depression Rating Scale (HDRS) were used to assess clinical symptoms. We tested serum UA concentrations by sandwich enzyme-linked immunosorbent assay (ELISA) at baseline and at the end of 8-week treatment in BPD patients and in the control group. Results After 8-week quetiapine and sodium valproate therapy, the concentrations of serum UA were significantly decreased compared to the pre-therapy baseline levels (t=3.361, p<0.001). Concentrations of UA were significant lower in remitted group than non-remitted group (t=2.07, p=0.04). There was a significant correlation between the changes of UA concentrations and their YMRS scores (r = 0.25, p = 0.03). Patients suffering manic disorder had higher serum UA than those remitted patients (378.55±99.08 vs. 323.57± 73.53 μmmol/L, p<0.001). All BPD patients had higher serum UA concentrations than healthy subjects (293.39±71.40 μmmol/L, all p<0.05). Conclusion Our results suggested that serum UA concentrations might present not only a biomarker of the state of mania, but also potentially a trait marker in bipolar patients. It could be a significant biomarker objectively estimating the treatment efficacy in patients suffering from BPD.